ANXIOLYTIC EFFECT OF CLONIDINE IN MICE - S.JEYA PONMARI,; M.SHANHI,; R.NAVAJOTHI, (International Journal of Pharma and Bio Sciences, 2013)
Anxiety disorders are the most common psychiatric disorders in the world among both children and adults. Benzodiazepines are more commonly used anxiolytic drugs. Since it is found that anxiety disorder patients have poorly regulated noradrenergic system, we have studied the anxiolytic effect of Clonidine a a2 agonist which reduces the sympathetic outflow. We evaluated the anxiolytic effect of Clonidine using pentylene tetrazole to induce anxiety. Pentylene tetrazole is a CNS stimulant which produces anxiety at lower doses and convulsions at higher doses. Anxiety is evidenced by increased grooming activity in mice. 18 naïve male adult mice were divided into three groups of 6 animals each, namely control, standard and test groups. 30 minutes prior to administration of PTZ control group received water for injection, standard group received injection diazepam and test group received Clonidine intraperitoneally. The test group of animals showed significant reduction in the duration and frequency of grooming activity and thus this study proved the anxiolytic effect of Clonidine.